The role of health education and physical activity in the prevention of obesity in pregnant women - Kulbat, Aleksandra; Karwańska, Aleksandra; Uniłowska, Izabela; Dovzhuk, Yuliia; Kojder, Ewa; Dolenha, Arsen; Ochał, Justyna; Matyka, Kamila; Ferschke, Anna; Szymczyk, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction: Obesity is a major health concern in pregnancy, and it can lead to various adverse outcomes for both the mother and the fetus. The increasing prevalence of obesity among pregnant women calls for effective strategies to prevent its occurrence and reduce its consequences. Health education and physical activity have been identified as potential interventions to prevent obesity in pregnant women. Aim of study: The aim of the review is to present the impact of physical activity and health education on obesity in pregnant women, as well as its pathogenesis and treatment. Materials and Methods: The authors followed the PRISMA guidelines to ensure high-quality work. The search was based on databases such as PubMed, Google Scholar, Scopus, and Web of Science, with a limitation to publications after. The strategy relied on search terms such as 'obesity in pregnancy', 'treatment', 'physical activity', 'health education', and 'sport', combined using 'AND' and 'OR' operators. The team members reviewed the abstracts and then decided on their inclusion in the study. Results: According to literature reviews, health education and physical activity can be effective interventions in preventing obesity in pregnant women. They can help prevent excessive weight gain during pregnancy and reduce the risk of gestational diabetes and other obesity-related complications. Individual dietary advice, exercise programs, and lifestyle modification counseling are recommended. However, further research is needed to determine the most effective strategies for preventing obesity in pregnant women and assessing long-term health outcomes. Conclusions: Both regular physical activity and health education can be useful in prevention and treatment of obesity during pregnancy, and should be included as part of a comprehensive approach to women's health during pregnancy. It is important for people to understand the benefits of regular physical activity throughout the entire pregnancy period.